Auditors' Subjective Decision Environment-The Case of a Normal External Audit. - Gibbins, Michael; Wolf, Frank M. (The Accounting Review, 1982)
Abstract ABSTRACT: A description was developed of external auditors' subjective decision environment in the case of a normal manufacturing company audit. Eighty partners and managers from six national public accounting firms in Canada responded to an extensive questionnaire asking them to evaluate potential environmental components at several stages in the audit engagement: (1) before the beginning of the work, (2) at several operational stages and (3) after the audit's completion. The audit environment was revealed to be complex: though some components were perceived to be consistently important throughout the audit, the importance of others waxed and waned as the audit progressed. A highly interdependent, client-oriented environment was portrayed by respondents.